2011
DOI: 10.1080/09593330.2011.589133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coconut granular activated carbon pretreatment on membrane filtration in a gravitational driven process to improve drinking water quality

Abstract: This study evaluates the performance of a polymeric microfiltration membrane, as well as its combination with a coconut granular activated carbon (GAC) pretreatment, in a gravitational filtration module, to improve the quality of water destined to human consumption. The proposed membrane and adsorbent were thoroughly characterized using instrumental techniques, such as contact angle, Brunauer-Emmett-Teller) and Fourier transform infrared spectroscopy analyses. The applied processes (membrane and GAC + membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The morphology of copper oxide nanoparticles was also analyzed by transmission electron microscopy (TEM). Figure 1 shows the gravitational filtration module used in this study, which was proposed in a previous study (Silva et al, 2012).…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of copper oxide nanoparticles was also analyzed by transmission electron microscopy (TEM). Figure 1 shows the gravitational filtration module used in this study, which was proposed in a previous study (Silva et al, 2012).…”
Section: Characterizationmentioning
confidence: 99%
“…Integration of a pretreatment with a membrane filtration process has been employed to reduce membrane fouling and to improve the removal of certain contaminants. It is reported that the combination of activated carbon with membrane filtration increased the obtained volume of filtrated water and prolonged the continuous filtration time by mitigating membrane fouling (Ajmani et al, 2012;Kim et al, 2009;Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al drew the same conclusion that PAC could majorly adsorb non-pollutants for the membrane, so the remaining membrane pollutants would bring more severe fouling [18]. Da Silva et al used the obtained fluxes, filtrating water artificially contaminated with E. coli as the influent, and found that the coupling of granular activated carbon (GAC) treatment with membrane filtration could obtain a higher initial flux with GAC pretreatment working with a clean membrane and the addition of GAC could also decrease the membrane fouling [31]. Park et al [32] and Milovic et al [33] employed the grampositive bacterium Staphylococcus aureus to investigate the bactericidal effect of the coatings and chose the microbicidal surface coatings based on immobilized hydrophobic polycations.…”
Section: Pretreatmentmentioning
confidence: 99%
“…Characterizing the performance of different types of granular filtration media has been the focus of various studies. da Silva et al [19] studied the performance of a polymeric microfiltration membrane, as well as its combination with a coconut granular-activated carbon pre-treatment, in a gravitational filtration module, to improve the quality of water destined to human consumption. Assessment of partial replacement of sand with manganese oxide-coated sand (MOCS) is studied by Kim and Jung.…”
Section: Introductionmentioning
confidence: 99%